Isolation of Three Novel Senecavirus A Strains and Recombination Analysis Among Senecaviruses in China - Guo, Zhenhua; Chen, Xin-xin; Ruan, Haiyu; Qiao, Songlin; Deng, Ruiguang; Zhang, Gaiping (Frontiers in Veterinary Science, 2020)
Senecavirus A (SVA), an emerging swine picornavirus of swine, is one of the causative agents of vesicular disease which is clinically indistinguishable from foot-and-mouth disease in pigs. Here, 3 cases of vesicular disease were reported which was caused by SVA in November 2018 in Henan, China. Three new SVA strains were identified and conducted a genetically evolutionary analysis. The isolates shared 98.1%-99.0% genomic pairwise identity to each other and had the highest similarity, of 98.3%-98.7%, with the American strain KS15-01, respectively. Phylogenetic analysis indicated that the Chinese prevalent strains could be clearly divided into cluster 1, cluster 2 and cluster 3. Furthermore, one isolate (HeNNY-1/2018) and two previously reported strains (HB-CH-2016 and SVA/CHN/10/2017) were identified as recombinants using several algorithms. It revealed that the recombination among SVA strains has occurred in China since 2016 or earlier. The findings of studies updated the prevalent status of SVA in China. Besides, the genetic evolution and recombinant events of SVA should be attracted more attentions in the future.